Research on the construction of technology intermediary innovation ecosystem and the growth of small and medium-sized enterprises: taking Wuhu General Aviation Innovation Park as an example - Hu, Xiaochi (International Journal of Global Economics and Management, 2024)
With the in-depth implementation of the "mass entrepreneurship and innovation" strategy in China, scientific and technological innovation has become the main driving force of economic development, and the transformation of scientific and technological achievements is the main channel of scientific and technological innovation, and is the key link of the close combination of science and technology and economy. However, at present, China's science and technology intermediary system is not perfect and the performance of innovation transformation is low, which brings huge problems to the development of small and medium-sized enterprises in the ecosystem. As the carrier of technology diffusion and achievement transformation, the science and technology intermediary and the innovation ecosystem built play a vital role. From the perspective of the construction of the science and technology intermediary innovation ecosystem, Innovative view of science and technology intermediary as the main body, Further study on Wuhu General Aviation Innovation Park through literature analysis method, questionnaire survey method and interview method, The two complementary assets of technology intermediary are selected as the explanatory variables, Introducing resource sharing and knowledge spillover as intermediary variables, To analyze the constructed theoretical framework and mechanism, At the same time, four theoretical frameworks from the perspective of science and technology intermediary innovation ecosystem, For the formation and improvement of the science and technology intermediary innovation ecosystem, the effective promotion of innovation transformation ability and the growth of small and medium-sized enterprises.